Сomparison of the impact studies of acrobatic rock-n-roll and ballroom dancing on the creation of a culture of movement of children of primary school age - T.M. Kravchuk; N.M. Sanzharova; O.O. Sliusar; A.I. Moisieiev (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The purpose. The aim of the study is to carry out a comparative analysis of the impact of acrobatic rock and roll and ballroom dancing on the formation of the culture of movements of children of primary school age. Research participant. The study involved 3 groups of girls 7-8 years only 45, 15 of them - a control group, which included girls who were not engaged in any sports, 15 - experimental group 1-girls who were engaged in acrobatic rock ' n ' roll and 15-experimental group 2 - girls who were engaged in sports ballroom dancing. Research methods: analysis of scientific and methodological literature, analysis of training programs on acrobatic rock and roll and ballroom dancing, visual screening on the card posture rating test "dynamic posture" test "wave" forward, methods of mathematical statistics. Results. The study identified the main indicators of the level of culture of movements of younger students, in particular: correct posture; plasticity and coordination of movements. It is proved that under the influence of acrobatic rock'n'roll and ballroom dancing almost all indicators of the culture of movements of girls of primary school age have improved, especially dynamic posture, plasticity and coordination of movements. While the performance of girls who did not play sports remained unchanged, or deteriorated. Conclusions. The study carried out a comparative analysis of the level of culture of movements of young athletes in rock and roll and ballroom dancing. There was no statistically significant difference between the indicators of the culture of movements of young athletes engaged in acrobatic rock ' n ' roll and ballroom dancing. However, the same comparison of girls engaged in dance sports with girls not athletes showed their lagging behind in most indicators, especially dynamic posture, plasticity and coordination.